The contribution of the representatives of the Siberian (Tomsk) mining and geological school to the developmet of mineral raw material base in Russia and abroad - Chubik Peter S.; Nikiforov Sergei I. (Федеральное государственное бюджетное образовательное учреждение высшего образования «Санкт-Петербургский горный университет», 2017)
This paper is devoted to the maturation and development of Siberian (Tomsk) mining and geological school one of the leading schools in Russia, which was created in the first third of the 20th century in Tomsk Technological Institute by V.A.Obruchev and M.A.Usov known to be outstanding Russian and Soviet geoscientists and members of the Russian Academy of Science. The article touches upon the participation of representatives of Siberian (Tomsk) mining and geological school to the exploration and development of mineral and raw material base of Siberia, Russia’s Far East, Central Asia. The information about the most important geological discoveries made by nurslings of Siberian (Tomsk) mining and geological school is provided.
Keywords: Siberian (Tomsk) mining and geological school; Tomsk Technological Institute; Tomsk Polytechnic University; Siberian Geological Survey; V.A.Obruchev; M.A.Usov; raw materials deposits